Pengaruh Kompetensi dan Budaya Organisasi terhadap Motivasi Kerja Serta Dampaknya pada Kinerja Pegawai Puskesmas Talang Bakung Kota Jambi - Yenti, Zesmi; Suryani, Arna; Yamali, Fakhrul Rozi (J-MAS (Jurnal Manajemen dan Sains), 2024)
The aim of this research is to describe the competence, organizational culture, motivation and performance of employees at the Talang Bakung Community Health Center, Jambi City and to analyze the partial and simultaneous direct and indirect influence of competence and organizational culture on employee motivation and performance, as well as to analyze work motivation on employee performance. To answer the research objectives, this research is supported by theoretical studies related to research variables, namely work discipline, work stress, work motivation and performance. Apart from that, the author also looked for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this study were employees of the Talang Bakung Community Health Center, Jambi City, totaling 53 employees with conditions in 2022. The data analysis technique used in this research is through path analysis followed by hypothesis testing through the F test (Simultaneous) and t test (Partial). From the path analysis tests carried out, it was found that competence and organizational culture had an influence on work motivation by 82.9% while the rest was influenced by other variants. Competence and organizational culture have an influence of 83.3% on employee performance at the Talang Bakung Community Health Center, Jambi City. This research concludes that competency, organizational culture, work motivation and employee performance are in good and high condition. In addition, competency and organizational culture partially and simultaneously have a positive and significant influence on work motivation and employee performance at the Talang Bakung Community Health Center, Jambi City. Likewise, work motivation has a positive and significant influence on employee performance.